Learning gain of pharmacy students after introducing guided inquiry learning with computer simulation in a pharmacology class in Fiji - Christian C Ezeala; Arnold A Ram; Napolioni Vulakouvaki (Journal of Educational Evaluation for Health Professions, 2013)
Purpose: Active learning methods such as problem-based learning have been widely adopted in health professions education, although guided inquiry learning has been used only in limited settings. The objective of this study was to determine students’ learning gain when guided inquiry learning was combined with computer simulation in a basic pharmacology course. Methods: The second-year pharmacy students from Fiji National University participated in the study. Following classroom lectures on pharmacokinetics and pharmacodynamics, the students used tutor-prepared practice problems in groups of 3-4 to explore their concepts with Cyber Patient and Virtual Organ Bath software. Pre- and posttest assessments were administered to determine the learning gain from the exercises based on Hake’s criteria. Results: Forty-two students participated in the study. The average normalized learning gain from the pharmacokinetics exercises was 0.68. Thirty-seven participants (88.1%) achieved a significant learning gain, while 5 (11.90%) did not. The average normalized learning gain from the pharmacodynamics exercises was 0.76. Forty-one participants (97.6%) achieved a significant learning gain, while one participant (2.4%) did not. Conclusion: These results demonstrated that use of guided inquiry learning with computer simulations could produce significant learning gains with improvement in students’ understanding of basic pharmacology.